A new approach to chest pain in the emergency room: “Triple rule-out” CT - (:unkn) unknown (My University, 2012)
Göğüs ağrısı tüm acil servis başvurularının önemli bir bölümünü oluşturan ve ciddi sonuçları olabilen bir sağlık sorunudur. Ayırıcı tanısı için birçok tetkik ve uzun takip süreleri gerekmektedir.. Aort, pulmoner damarlar ve koroner damarların aynı anda görüntülenebilmesini sağlayan yeni bir bilgisayarlı tomografi tekniği olan “triple rule-out” teknolojik altyapısındaki yeni gelişmelerle akut göğüs ağrısı takip protokollerini değiştirmeye aday bir tanı yöntemidir. Bu yazıda şu ana kadar konuyla ilgili yapılmış çalışmalar ışığında triple ruleout BT’nin acil serviste kullanılabilirliği tartışılmaktadır. (JAEM 2012; 11: 41-6)

Chest pain constitutes an important part of all emergency room visits and can lead to serious heath problems. Generally the differential diagnosis and follow-up period should be long lasting. Triple rule-out computed tomography is a new technique which can provide visualization of coronary arteries, pulmonary vasculature and aorta with a single shot. With rapidly developing technologies, it becomes a candidate for changing the “acute chest pain” follow-up protocols. In this review we attempt to discuss the applicability of triple rule-out CT in the emergency room in the light of new studies on the issue. (JAEM 2012; 11: 41-6)
Acil serviste göğüs ağrısına yeni bir yaklaşım: “Triple rule-out” BT
Keywords: Acil Tıp